Environmental Pollutants and Metabolic Disorders: The Multi-Exposure Scenario of Life - Le Magueresse-Battistoni, Brigitte; Vidal, Hubert; Naville, Danielle (Frontiers in Endocrinology, 2018)
Obesity and diabetes have reached epidemic proportions the past few decades and continue to progress worldwide with no clear sign of decline of the epidemic. Obesity is of high concern because it is the main risk factor for a number of non-communicable diseases such as cardiovascular diseases and type 2 diabetes. Metabolic diseases constitute a major challenge as they are associated with an overall reduced quality of life and impose a heavy economic burden on countries. These are multifactorial diseases and it is now recognized that environmental exposure to man-made chemical pollutants is part of the equation. Yet, risk assessment procedures are based on a one-by-one chemical evaluation which does not meet the specificities of the multi-exposure scenario of life, e.g. a combined and long-term exposure to even the smallest amounts of chemicals. Indeed, it is assumed that environmental exposure to chemicals will be negligible based on the low potency of each chemical and that they do not interact. Within this mini-review, strong evidences are brought that exposure to low levels of multiple chemicals especially those shown to interfere with hormonal action, the so-called endocrine disrupting compounds do trigger metabolic disturbances in conditions in which no effect was expected if considering the concentration of each individual chemical in the mixture. This is known as the cocktail effect. It means that risk assessment procedures are not protective enough and thus that it should be revisited for the sake of Public Health.